PROSES DAN PENGALOKASIAN DANA ALOKASI KHUSUS KABUPATEN ACEH TIMUR - Syahrial Syahrial (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2016)
The objective of the research is evaluating the process of arrangement of expenditure budget in Kabupaten Aceh Timur that include the role of DPRD as people representative. Evaluating amount of expenditure budget allocation Kabupaten Aceh Timur to public service and institution/executor service. The used data is qualitative data and quantitative data from Kabupaten Banjar budget starting year 2010 – 2014, that gotten from Finance Department, Program Arranging Department, Dipenda and Bapedda Kabupaten Aceh Timur. The research uses Descriptive Analysis and Comparative Budget Statement (CBS) Analysis. The result of the research shows that the process of arrangement of district income and expenditure at Kabupaten Aceh Timur has not expressed the local inhabitants aspiration, where most of direction and common policy of budget dominated and express the high government aspiration and no optimal role of budget committee of district legislative assembly Kabupaten Aceh Timur as people representative in region if compared by the role of executive budget committee. From year 2010 – 2014 average of expenditure allocation of public service achieve 61,51%, while expenditure of bureaucracy service is 38,49%, but average routine expenditure is still greater than development expenditure, that is 60,88% and 39,12%.